X SOSTITUZIONE.
Spiegare il ragionamento e argomentare.
∫(x/(x + 1)^5) dx =
= - x/(4·(x + 1)^4) + ∫(1/(x + 1)^4)dx/4=
(per parti)
=- x/(4·(x + 1)^4) - 1/(12·(x + 1)^3)=
=- (4·x + 1)/(12·(x + 1)^4)
Valutato in x =2:
- (4·2 + 1)/(12·(2 + 1)^4)= - 1/108
Valutato in x = 0
- (4·0 + 1)/(12·(0 + 1)^4) = - 1/12
Quindi: - 1/108 - (- 1/12) = 2/27
$\int_0^2 \frac{x}{(x+1)^5} \, dx =$ per sostituzione.
Poniamo $ t = x+1 \; ⇒ \; x = t-1 \; ⇒ \; dx = dt$
inoltre Se x = 0 allora t = 1; Se x = 1 allora t=3
$\int_1^3 \frac{t-1}{t^5} \, dt =$
$\int_1^3 t^{-4} -1 \cdot t^{-5} \, dt =$
$= \left. -\frac{1}{3t^3}+3\frac{1}{4t^4} \right|_1^3 =$
$ = \left. \frac{-4t+3}{12t^4} \right|_1^3 =$
$ = -\frac{1}{12 \cdot 9} + \frac{1}{12} =$
$ = \frac {2}{27} $